Real Scenarios for Teaching English in Public Elementary Schools in Colombia (2021)
ABSTRACT: This literature review aims to gather information about the reality of teaching English in public elementary schools in Colombia; from what has been published, eight articles were chosen and analyzed. From the articles reviewed, three categories arose: The differences between the written law and guidelines and the reality in the classrooms, the lack of preparation of the teacher to teach English in elementary school and the lack of didactic materials. However, some teachers and pre-service teachers have made efforts to implement updated methodologies, proving that there are other possibilities.